Quality Audit Roles and Skills: Perceptions of Non-Financial Auditors and their Clients - Power, D.; Terziovski, Mile (Elsevier BV, 2007)
A major development in Operations Management over the past two decades has been the use of quality audits to gauge the effectiveness of quality management systems in manufacturing and service organizations. Achieving optimal benefits from nonfinancial audits will, however, require that auditors and their clients obtain a greater understanding of and appreciation for the appropriate roles, responsibilities and skills of the non-financial auditor. This research uses data obtained from surveys of 126 practicing non-financial auditors and 400 non-financial audit clients in Australasia to test two propositions about the roles and requirements of non-financial auditors. The results indicate that non-financial auditors believe they are providing a style of auditing that is strongly focused on developing continuous improvement of client’s quality systems. Non-financial auditors also appear to have a desire to meet what they perceive to be the requirements of certified organizations by emphasizing the importance of continuous improvement focused auditing. However, their clients have the opposite perception believing that they are getting less continuous improvement focused auditing than they would like, and more compliance auditing than they need. The results show that client organizations are, in general, looking for a more balanced approach to non-financial auditing in terms of compliance and continuous improvement. The evidence also suggests that a major constraint identified relates to some fundamental issues of auditor independence. This dilemma created is apparent both in the understanding of what the appropriate role of the auditor is (in both the mind of the client and the auditor), and in the nature of the different roles each plays as a stakeholder in a quality system. # 2006 Elsevier B.V. All rights reserved.